1993
DOI: 10.1007/bf02096643
|View full text |Cite
|
Sign up to set email alerts
|

Perturbative renormalization of composite operators via flow equations II: Short distance expansion

Abstract: We give a rigorous and very detailed derivation of the short distance expansion for a product of two arbitrary composite operators in the framework of the perturbative Euclidean massive Φ^ The technically almost trivial proof rests on an extension of the differential flow equation method to Green functions with bilocal insertions, for which we also establish a set of generalized Zimmermann identities and Lowenstein rules. 2) ^ 0); 2.4. The renormalization conditions (D (1>2) ^ 0); 2.5. Perturbative renormaliza… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
69
0
1

Year Published

1994
1994
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(73 citation statements)
references
References 10 publications
3
69
0
1
Order By: Relevance
“…Remarkably, for Euclidean perturbative φ 4 -theory, it has been shown that the series on the right side actually converges, at least at arbitrary but fixed order in perturbation theory [51,63]. If, as we expect, this also were found to be true at spacelike related points for theories on Lorentzian curved spacetimes, then this would strongly reinforce the view that the OPE coefficients contain the entire local information about the theory, even on a curved spacetime.…”
Section: Nonperturbative Formulation Of Interacting Qftcssupporting
confidence: 53%
See 1 more Smart Citation
“…Remarkably, for Euclidean perturbative φ 4 -theory, it has been shown that the series on the right side actually converges, at least at arbitrary but fixed order in perturbation theory [51,63]. If, as we expect, this also were found to be true at spacelike related points for theories on Lorentzian curved spacetimes, then this would strongly reinforce the view that the OPE coefficients contain the entire local information about the theory, even on a curved spacetime.…”
Section: Nonperturbative Formulation Of Interacting Qftcssupporting
confidence: 53%
“…We consider a massless quantum Klein-Gordon scalar field in the spacetime (63). This is a (slight) simplification of the more physically relevant problem of starting with a classical solution of the Einstein-scalar-field system with scalar factor of a form approximating (63)-as would occur if the scalar field "slowly rolls" down an extremely flat potential-and then treating the linearized perturbations of this system as quantum fields.…”
Section: D) Cosmological Perturbationsmentioning
confidence: 99%
“…FRG formulations are also suitable for both discussing formal aspects as well as practical applications. The FRG has been introduced with a smooth momentum cut-off for simplifying proofs of perturbative renormalisability and the construction of effective Lagrangians in [6], see also [9,[31][32][33]. More recently, there has been an increasing interest in FRG methods as a computational tool for accessing both perturbative as well as non-perturbative physics, initiated by [10][11][12][13][14].…”
Section: Flowsmentioning
confidence: 99%
“…Using a cut-off function with compact support, Polchinski gave a simple proof of the power-counting renormalization theorem; the proof has been generalized and further simplified in [5,23,24,7]. Analogous results have been obtained using an exponential cut-off in [25]; a proof of renormalizability with a Pauli-Villars cut-off, like that of eq.…”
Section: Exact Renormalization Groupmentioning
confidence: 98%